Law Enforcement of Pirated Film User Sites Due to the Implementation of Physical Distancing in Denpasar - Sudharma, Kadek Januarsa Adi; Kurniawan, I Gede Agus; Pratama Sanjaya, Putu Ngurah Dhimas; Asmari, Dewa Ayu Yeni (Kertha Patrika, 2022)
The purpose of this study was to determine the effectiveness of the application of the Copyright Act to the number of pirated movie sites viewers as the impact of physical distancing in Denpasar City. This research was empirical legal research that examines the expectations and using a descriptive qualitative manner. This research population was Denpasar City residents, with a random sample of 172 respondents filled in an online questionnaire. The results indicated that decreased the percentage of pirated film provider sites before and during COVID-19 by 21,7%. That was influenced by the proportion of the time and costs spent watching movies on legal sites and also the blocking of pirated film sites by the government. After looking at the data and reviewing it with the theory of legal effectiveness and legal protection, it concludes that as long as physical distancing implemented, the Copyright Law enforcement has not been going well and must be corrected in one way. It was namely replacing the complaint offence contained in it with an ordinary offence.